Sejarah Politik dan Dinamika Agraris Kawasan Timur Indonesia - Tri Pranadji (Pusat Sosial Ekonomi dan Kebijakan Pertanian, 2010)
EnglishFrom the agrarian politic history view, the eastern region of Indonesia has a relatively strong competition potential in the global arena. However, since the past five decades, the capacity of socio-economic-politic-culture of the eastern region of Indonesia was degraded to the lowest level. The political planning concern of the central government in the agrarian resource development management is the obstacle point to allow serious implication on social gap and backwardness. The agrarian politic set back in the western part of Indonesia has a heavy influence on the community’s socio-economic livelihood who are depending on local agrarian resources. The prominent ability of several local kings of kingdoms in the eastern Indonesia to perform agricultural trade at a global level during the period of 15-18 centuries has no longer existed. In the future, a strong political support is required to reform agrarian development planning for the eastern region of Indonesia. The plan should cover: First, the vision and direction to establish a strong, self-support, high competitive, fair, and sustainable industrial community based on the existing agrarian resource management. Second, to produce high value of agrarian products, manage by integrated organizations, use high technology and innovation, apply sharing system on collective assets, and select appropriate business adjusted to the existing local agro-ecosystems. Third, strengthen infrastructure networks, support financial institutions, and apply law enforcement in accordance with good governance in a decentralized government administration. Fourth, to establish the community’s rights to express their political opinion and aspiration, to involve in organization (economic, society, and politic), and support on local wisdom. Fifth, to perform policies that integrates agrarian management, safety and defense, and the empowerment of civil society in the eastern part of Indonesia.IndonesianDilihat dari sejarah politik agraria, kawasan timur Indonesia mempunyai potensi daya kompetisi relatif kuat dalam “pertarungan” global. Hanya saja, sejak lima dekade terakhir secara sosio-ekonomi-politik-budaya kawasan timur Indonesia berbalik menjadi sangat memprihatinkan. Kepedulian politik perencanaan pemerintah pusat dalam pengembangan pengelolaan sumber daya agraria setempat tampaknya menjadi titik lemah yang berimplikasi serius terhadap munculnya keterbelakangan dan kesenjangan sosial. Kemunduran politik agraria yang terjadi di kawasan barat Indonesia berimbas sangat berat terhadap tingkat kehidupan sosial-ekonomi masyarakat berbasis pengelolaan sumber daya agraria setempat. Kehebatan kemajuan perdagangan produk agraris yang dikendalikan secara politik di tingkat global oleh beberapa kerajaan di kawasan timur Indonesia pada rentang abad 15-18 saat ini sudah hampir tidak tersisa lagi. Pada masa mendatang perlu dukungan politik yang kuat untuk merumuskan kembali perencanaan pembangunan agraria di kawasan timur Indonesia. Substansi perencanaan mencakup: Pertama, visi dan arah yang mengutamakan terbentuknya masyarakat industrial berbasis pengelolaan sumber daya agraria yang kuat, mandiri, berdaya saing tinggi, adil, dan berkelanjutan. Kedua, dihasilkannya produk agraria bernilai tambah tinggi, dikelola dengan organisasi yang utuh (tidak tersekat-sekat), sarat dengan muatan iptek tinggi, penguasaan aset secara kolektif dengan sharing system yang lebih adil, serta pilihan usaha yang sesuai dengan kekayaan agroekosistem setempat. Ketiga, dilakukan penguatan terhadap jaringan infrastruktur, kelembagaan modal finansial, penegakan hukum, serta good governance dalam penyelenggaraan pemerintahan yang desentralistik. Keempat, penguatan hak-hak warga dalam berpendapat dan beraspirasi secara politik, berorganisasi (ekonomi, kemasyarakatan, dan politik), serta pemberdayaan aspek kearifan lokal. Kelima, kebijakan politik yang mengintegrasikan pengelolaan agraria, pertahanan dan keamanan, serta penguatan civil society di kawasan timur Indonesia.